Impact of Gingival Margin Asymmetries on the Smile Esthetic Perception of Dental Specialists, Doctors of Dental Medicine, Students, and Laypeople: a Comparative Pilot Study - Martina Čalušić Šarac; Sandra Anić Milošević; Domagoj Vražić; Marko Jakovac (Acta Stomatologica Croatica, 2022)
Objective: To evaluate the perceptions of altered incisor gingival position among dental specialists, dentists, dental students, and laypeople. Material and methods: Four digital smile photographs with altered gingival margin position of the right maxillary incisor (0, 1, 2, and 3 mm) were presented to a sample of 232 respondents (71.1% female; 28.9% male): 42 dental specialists, 63 dentists, 33 dental students (1 st to 3 rd year), 38 dental students (4 th to 6 th year) and 56 laypeople. The questionnaire consisted of four randomly displayed photographs, administered via Google Form, and respondents were asked to rate the images on a scale from 1 to 5, from the least attractive to the most attractive. A statistical analysis was performed using the TIBCO Statistica program (v. 13.3. 0, TIBCO Software Inc., Palo Alto, CA, USA; 2017). According to the Shapiro- Wilk’s test, the data were not distributed normally. The Kruskal-Wallis test with post hoc multiple comparisons with the Bonferroni adjustment were used to compare group esthetic scores and to determine the threshold levels of deviation at which each group was discriminated between esthetic and non-esthetic situations. Results: Median values of esthetic scores decreased in all groups as the gingival asymmetries increased. Dental professionals were significantly more critical of esthetics than laypeople in all levels of asymmetry. The greatest difference was found for 2 mm of gingival asymmetry (p=0.002). Conclusion: From the results of our study, we can conclude that the perception of gingival asymmetries in the esthetic zone of smile differs among dental specialists, doctors, students, and laypeople. Dental specialists, doctors, and clinical students were more critical of these asymmetries, while preclinical students and laypeople noticed only 2 mm or more of gingival asymmetry of central incisors.